2020
DOI: 10.3390/nu12092734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Nitrates on Time Trial Performance in Athletes with Different Training Status: Systematic Review

Abstract: Much research has been done in sports nutrition in recent years as the demand for performance-enhancing substances increases. Higher intake of nitrates from the diet can increase the bioavailability of nitric oxide (NO) via the nitrate–nitrite–NO pathway. Nevertheless, the increased availability of NO does not always lead to improved performance in some individuals. This review aims to evaluate the relationship between the athlete’s training status and the change in time trial performance after increased dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 113 publications
0
11
0
2
Order By: Relevance
“…In this regard, CIT [ 12 , 13 , 14 , 15 , 17 ] and BR (NO precursors) [ 23 , 25 , 26 , 30 , 31 , 32 ] are two nutritional supplements that could help improve performance in both exercises, involving neuromuscular strength and endurance [ 56 , 57 ]. It has been shown that NO can help athletes with functions that are closely involved in the regulation of muscle contraction, blood flow, maximal oxygen consumption during exercise, adaptations at the mitochondrial level and homeostasis of glucose and calcium [ 27 , 57 , 58 , 59 ], which in the long term can improve athletic performance [ 60 ]. These NO precursors may also improve performance in maximal and endurance strength and aerobic power tests through an increase in ATP production, improvement in contractile function and a decrease in ammonium, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, CIT [ 12 , 13 , 14 , 15 , 17 ] and BR (NO precursors) [ 23 , 25 , 26 , 30 , 31 , 32 ] are two nutritional supplements that could help improve performance in both exercises, involving neuromuscular strength and endurance [ 56 , 57 ]. It has been shown that NO can help athletes with functions that are closely involved in the regulation of muscle contraction, blood flow, maximal oxygen consumption during exercise, adaptations at the mitochondrial level and homeostasis of glucose and calcium [ 27 , 57 , 58 , 59 ], which in the long term can improve athletic performance [ 60 ]. These NO precursors may also improve performance in maximal and endurance strength and aerobic power tests through an increase in ATP production, improvement in contractile function and a decrease in ammonium, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a meta-analysis of such studies conducted up until 2015 reported an overall effect size of 0.26 (0.15-0.38, p < 0.0001) for the reduction in oxygen utilisation during sub-maximal exercise, with effects being greatest during moderate and heavy intensity exercise [57]. Variability in findings around effects of nitrate supplementation on both economy and performance can be explained, in theory [19,56] and by meta-analysis, by a number of factors including the supplementation protocol (amount, type and timing) [58], the type of exercise [57] and the training status and aerobic fitness of the subject group [59,60]. The apparent lack of effect in elite endurance athletes may be a function of their athletic status (e.g., due to a superior background NO production or reduced number of Type II muscle fibres in which nitrate supplementation might be most suited to targeting conditions of hypoxia or acidosis [19,56,61,62]) as well as an interaction with the conditions of use.…”
Section: Discussionmentioning
confidence: 99%
“…El NO es conocido como un potente vasodilatador que favorece la irrigación sanguínea hacia los músculos, mejorando el aporte de sustratos energéticos para la respiración aeróbica como oxígeno, ácidos grasos, glucosa; así como la remoción de intermediarios y desechos metabólicos (Betteridge et al, 2016). Además, el rol ergogénico de la producción de NO parece estar relacionado con el tipo de fibra muscular, siendo las fibras tipo II (glucolíticas de contracción rápida) las que se verían más beneficiadas (Hlinský et al, 2020 et al, 2009). La mayoría de los estudios de intervención que han evaluado el impacto del NO 3 sobre el rendimiento deportivo, se han realizado con jugo de remolacha.…”
Section: Nitratounclassified
“…El efecto ergogénico se ha reportado mayormente en hombres jóvenes, sanos y que realizan actividad física recreativa, aunque el efecto de la suplementación se considera leve (Senefeld et al, 2020). Los efectos ergogénicos del NO 3 se han reportado mayormente en protocolos de suplementación crónica y no en suplementación aguda (Hlinský et al, 2020).…”
Section: Nitratounclassified